BAGGAGE AT AIR TRANSPORTATION AS A SUBJECT OF CRIME: COMPLEX CHARACTERISTICS - Семчук, Наталя Олександрівна; Хоцяновська, Наталя Францівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
As the title implies the article describes legal regime for baggage .In the process of emergence as a European state, Ukraine needs effective aviation interstate and national communications. Efficiency of air transportation is an integral part of the formation of a stable economy and the development of international relations. Efficient international air transportation of passengers is able to provide labor migration and investment development. Purpose: to carry out a comprehensive description of baggage during air transportation as a subject of crime, taking into account air-law, civil law, criminal law, forensic and logistic aspects. The legal regime of baggage during air transportation and its characteristics as a subject of crime were studied. Research methods: used methods of analysis, comparison and synthesis. The results: obtained the conclusion that the baggage for air transportation as a crime has a special legal regime. A special legal regime for baggage requires research in the aspect of many branches of knowledge. The main aspects that contribute to the occurrence of violations in this area is that the baggage is out of the passenger’s observation, and airport employees, on the contrary, have full access to it and even the possibility for manual inspection. Forensic aspects of the study require an integrated approach. For the practical investigation of these crimes, it is necessary to create special investigative groups involving various state institutions. Discussion: the necessity of developing complex civil, air-legal and forensic recommendations for the qualification and investigation of crimes, the subject of which is baggage during air transportation, is substantiated. Depending on the specific situation, liens can be classified as: theft if the cost of the stolen has reached the limits of criminal responsibility, willful destruction or damage to property if it caused damage in large quantities, careless destruction or damage to someone else’s property, when such destruction or damage to baggage has caused grave bodily harm or death of people, official negligence if the passenger has suffered material damage and has a sign and officer.